Trends in carbapenem antibiotics utilization, costs, and market dynamics in Medicaid: a retrospective analysis from 1991 to 2023 - Alrasheed, Marwan A.; Alsuhibani, Abdulrahman A. (Frontiers in Medicine, 2025)
BackgroundCarbapenems are vital antibiotics used to treat severe infections, particularly those caused by multidrug-resistant organisms. Understanding their utilization, reimbursement, and pricing trends is critical to inform healthcare policies and ensure sustainable access. This study aimed to analyze longitudinal trends in carbapenem use, market dynamics, and economic impact within Medicaid from 1991 to 2023.MethodsA retrospective, longitudinal analysis was conducted using publicly available Medicaid State Drug Utilization data. Four carbapenems; imipenem/cilastatin, meropenem, ertapenem, and doripenem were examined. Data on prescriptions, reimbursements, and proxy pricing were extracted, aggregated, and analyzed. Trends and market shares were evaluated annually, with statistical analyses and visualizations performed using Excel and Power BI. Joinpoint regression analysis was used to identify shifts in the direction of these trends, providing insights into significant changes over time.ResultsCarbapenem utilization and reimbursement exhibited significant growth, particularly between 2015 and 2020, driven by increased reliance on these agents for severe infections. Imipenem/cilastatin prescriptions peaked in 2005 at 22,883 prescriptions, with an Annual Percent Change (APC) of 12.28% (95% CI: 11.33 to 14.03%, p < 0.001). Reimbursements for imipenem/cilastatin reached 7.6 million in the same year. Following 2005, a sharp decline in prescriptions occurred, with an APC of −30.36% (95% CI: −33.96% to −25.44%, p < 0.001), and reimbursements dropped to 839,581 by 2023. Meropenem prescriptions exhibited steady growth, peaking at 53,355 in 2016, with an Average Annual Percent Change (AAPC) of 17.29% (95% CI: 13.97 to 29.71%, p < 0.001). Reimbursements for meropenem reached 10.9 million in 2016 before stabilizing at 7.2 million in 2023. Ertapenem, introduced in 2002, demonstrated the most substantial growth, peaking in 2021 with 116,988 prescriptions and 30.7 million in reimbursements. Its APC between 2002 and 2015 was 19.05% (95% CI: 13.56 to 109.30%, p = 0.023). Doripenem prescriptions peaked at 2,954 in 2011 but declined sharply at an APC of −39.24% (95% CI: −52.08% to −35.15%, p < 0.001), with reimbursements dropping to negligible levels by 2017. Declines in carbapenem prescriptions and reimbursements after 2021 reflect antimicrobial stewardship efforts and shifts toward targeted therapies.ConclusionThis study underscores dynamic shifts in carbapenem utilization, highlighting the impact of clinical practices, stewardship initiatives, and policy changes on prescribing trends. Continuous monitoring of antibiotic use is essential to balance effective infection management with the containment of antimicrobial resistance and healthcare costs. Further research is needed to evaluate the long-term effects of stewardship programs and the introduction of novel therapeutic options on carbapenem utilization.